Landscapes and the Archaeology of the Ifugao Agricultural Terraces: Establishing Antiquity and Social Organisation - Acabado, Stephen (Hukay; Vol 15 (2010))
This paper provides a summary of the results of an archaeological and landscape survey in Banaue, Ifugao carried out in 2007. This survey is part of a larger study that explores the relationship between irrigation management and social organisation of the Ifugao in the Northern Philippines. This historical ecological study examines the sustainability of Ifugao irrigated ‐ terrace farming, and documents dynamic and recursive linkages between the Ifugao and their environment. Its focus on the apparent disjunction between water management and sociopolitical stratification, identifies factors that underlie the sustainability of Ifugao agriculture, and structural correlates that generate an intensive agricultural landscape.   The sustainability of Ifugao agriculture is related to the social structure that links individuals through attachment to the agricultural field. As such, this investigation establishes the nature of Ifugao social organisation through the “house” concept. Corollary to determining cultural patterns in Ifugao, this project aims to resolve debates on the antiquity of the entire Cordillera terraced field tradition. Archaeological and ethnohistoric work will confirm whether the conventional ‘long history’ or the revisionist ‘short history’ more accurately represents the occupational history of this region.